Pleurothallis silvae-pacis, a new species - Karremans Lok, Adam Philip (2011)
Costa Rica is well-known for its outstanding programmes aimed at conserving the local flora and fauna. The country has a large number of protected areas spanning vast expanses of public property. The Bosque de Paz Biological Reserve is a good example of this. Although it is known mainly for its mountain lodge, which is an eco-tourism destination, it also has a small research centre, with a botanical library, herbarium and dissecting equipment. One such species found at Bosque de Paz was Pleurothallis silvae-pacis.